THE INFLUENCE OF KNOWLEDGE, INFORMATION AND RELIGIOSITY ON THE ZAKAT DECISIONS OF PT TRANS RETAIL INDONESIA EMPLOYEES - M. Wawang Darmawan; Eka Sutisna; H. Fikriah; Syamsul Bahri (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The research aims to determine the perception of Transmart employees towards zakat. The variable used in this study are the cariables of knowledge,information, and religiosity. This research is a quantitative study, data collected usig google form. The result showed that the variable knowledge did not affect the decision to pay zakat, while information and religiosity affected the decision to pay zakat. The decision of society towards Zakat needs to supported by massive socialization and education. Of course, proper regulation also need to be prepared in order to achieve the goals of zakat.